Developing leadership for pre-service teachers: previous concepts and models - Amirul Fahmie Abdul Razak; Muhammad Faizal A. Ghani; Norfariza Mohd Radzi; Nur Diyana Zakariah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Developing leadership skills among pre-service teachers is a pressing issue that is vital for ensuring the long-term sustainability and continuous advancement of the educational landscape. The purpose of this concept paper is to examine the role of pre-service teacher leadership in shaping future educational environments. Drawing upon theoretical frameworks and empirical research related to pre-service teacher leadership, this paper highlights the significance and dimensions of pre-service teacher leadership. Six common aspects crucial for developing leadership qualities in pre-service teachers are identified: (i) empowering professional leadership, (ii) setting direction, (iii) enriching data practices, (iv) valuing diversity, (v) fostering stakeholder consensus, and (vi) developing self competence. Through a comprehensive literature review and critical analysis of existing studies, the paper offers practical recommendations for integrating leadership initiatives within teacher education programs, emphasizing experiential learning, mentorship, and professional development. These recommendations aim to empower future educators and improve the overall quality of education. The implications of this paper suggest that incorporating structured leadership development programs into teacher education curricula can enhance pre-service teachers' readiness to face educational challenges and contribute positively to school communities. Furthermore, the integration of leadership skills may improve classroom management, instructional quality, and student engagement. Future research should explore the long-term effects of leadership development on pre-service teachers' career trajectories, as well as its broader impact on educational outcomes, such as student achievement and institutional improvement.